Review on Pull-out Test of Bolted Connection to Concrete Filled Hollow Section - Jeo Amran, Nurul Izzati; Abd Rahman, Norashidah (Recent Trends in Civil Engineering and Built Environment, 2023)
Bolted connection is one of the steel connection that been used widely during construction due to its flexibility and cost beneficial. The bolted connection to the hollow section itself will have the difficulties of stiffness due to inherent flexibility. Therefore, bolted connection to concrete filled hollow section (CFHS) was introduced. CFHS has proven in enhancing the stiffness and the strength compared to unfilled hollow section. However, the bolted connection behaviour could be varying due to types of concrete, grade of concrete and the bolt size. The aim of this study is to review the behaviour of bolted connection to CFHS. Difference type of bolted connection under monotonic pull-out test is reviewed. The type of bolt will discussed are AJAX Modified blind bolt, hollo bolt, extended hollo bolt, anchorage bolt, double headed anchorage bolt and M16 standard bolt. From the review analysis, the concrete types and grade play a major role in determining the behaviour of bolted connection to CFHS.